2021
DOI: 10.3390/foods10091970
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Parameters, Phytochemical Profile and Antioxidant Properties of a New Beverage Formulated with Xique-Xique (Pilosocereus gounellei) Cladode Juice

Abstract: This study elaborated different formulations with xique-xique (Pilosocereus gounellei) cladode, passion fruit and lime juice and sugar cane syrup. The formulated beverages were subjected to physical and physicochemical analysis, determination of total carotenoid, total flavonoid and total phenolic compound contents, as well as of their antioxidant activity (ABTS and FRAP method), organic acid, sugar and phenolic compound profile during 21 days of refrigeration storage (4 °C). Significant variations were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These are significant active ingredients with antioxidant activity, and the reduction in these ingredient contents under high-temperature storage conditions is closely related to the decrease in antioxidant activity of the system. Many studies have demonstrated that the total polyphenol content of plant extracts and plant beverages are positively correlated with the antioxidant activities of the systems ( Chen et al, 2015 , De Oliveira et al, 2021 , Roy et al, 2010 ). However, the polymerization of proteins with phenolic compounds and lipids may be the primary reason for the decreased total phenolic content.…”
Section: Resultsmentioning
confidence: 99%
“…These are significant active ingredients with antioxidant activity, and the reduction in these ingredient contents under high-temperature storage conditions is closely related to the decrease in antioxidant activity of the system. Many studies have demonstrated that the total polyphenol content of plant extracts and plant beverages are positively correlated with the antioxidant activities of the systems ( Chen et al, 2015 , De Oliveira et al, 2021 , Roy et al, 2010 ). However, the polymerization of proteins with phenolic compounds and lipids may be the primary reason for the decreased total phenolic content.…”
Section: Resultsmentioning
confidence: 99%
“…According to Nunes et al [ 116 ], the technological applications and the economic potential of these species can also be extended to their consumption in the form of gum candies, sweets, and juices. In the current literature, Oliveira et al [ 117 ] elaborated on a new mixed drink formulated with juice from the cladode xique-xique ( Pilosocereus gonellei ). The authors reported that incorporating cladode juice from xique-xique into these mixed drinks potentiated its bioactive properties, mainly of antioxidant compounds, allowing the development of a new product with potential functional properties for the beverage industry.…”
Section: Future Trends For Technological Application Of Cacti-derived...mentioning
confidence: 99%